The Effects of Radiotherapy on Microhardness and Mineral Composition of Tooth Structures - Siripamitdul, Patcharawat; Sivavong, Pimduean; Osathanon, Thanaphum; Pianmee, Chawalid; Sangsawatpong, Wiroj; Bunsong, Chalermchart; Nantanapiboon, Dusit (European Journal of Dentistry, 2022)
Objective The purpose of this study was to evaluate the microhardness and mineral composition alterations in enamel and dentine after radiotherapy.Materials and Methods Forty human maxillary premolar teeth (20 pairs) were assigned to nonirradiated and irradiated groups, the latter irradiated by fractional radiation to achieve a total dose of 70 Gy. Microhardness measurement was performed on a Knoop microhardness tester. Chemical components were analyzed using energy dispersive spectroscopy and Fourier transform Raman spectroscopy. The morphology was observed using a scanning electron microscope. The microhardness data were analyzed using a paired t-tested and one-way repeated analysis of variance (ANOVA), and the mineral composition data using related-samples Wilcoxon signed rank test and related-samples Friedman's two-way ANOVA by ranks.Results The irradiated teeth had a significantly lower microhardness in both enamel and dentine compared with the nonirradiated teeth. The irradiated dentine at 50 μm from the external tooth surface at the cemento-enamel junction showed the lowest microhardness compared with other locations. There was no statistically significant difference in calcium:phosphate ratio and chemical components. There was a reduction in protein:mineral ratio in dentine and at the cemento-enamel junction after irradiation. The irradiated teeth exhibited crack lines at the dentine-enamel junction and in dentine.Conclusion Fractional radiation reduced microhardness in both enamel and dentine. The cervical dentine exhibited the highest microhardness reduction compared with other enamel and dentine locations.
Keywords: radiotherapy; tooth structure; microhardness; SEM-EDS; FT-Raman